Cervical Cancer Screening Service Utilization and Associated Factors Among Women Living With HIV Receiving Anti-Retroviral Therapy at Adama Hospital Medical College, Ethiopia - Zubeyda Kedir Mohamed MSc; Yirga Wondu Amare MSc; Mihiret Shawel Getahun MPH; Yohannes Mekuria Negussie BSc; Abenet Menene Gurara MSc (SAGE Publishing, 2023)
Introduction Cervical cancer is the second highest cause of cancer-related mortality in the world, and it is one of the top 20 causes of mortality in Ethiopia. Even though cervical cancer is more common among women living with HIV, the utilization of cervical cancer screening services remains low in Ethiopia. Objectives This study aimed to assess cervical cancer screening service utilization and associated factors among women living with HIV receiving anti-retroviral therapy at Adama Hospital Medical College, Ethiopia. Methods An institution-based cross-sectional study was conducted among a sample of 304 women living with HIV from 1st-30th June 2022. Data were collected using an interviewer-administered questionnaire. The data were entered into Epi info version 7 and exported to SPSS version 25 for analysis. Bi-variable logistic regression analysis was used to identify candidate variables at p  < .25. Finally, multivariable logistic regression analysis was used to identify the independent predictors of cervical cancer screening service utilization at p  < .05 with 95% confidence intervals. Results The magnitude of cervical cancer screening service utilization was 26.9% (95% CI: 22.0, 32.6). Being a government employee (AOR: 8.09, 95% CI: 1.5, 41.19), having a family history of cervical cancer (AOR: 3.4, 95% CI: 1.02, 11.9), being aware of cervical cancer screening (AOR: 3.75, 95% CI: 2.11, 14.7), having a history of sexually transmitted infection (AOR: 3.14, 95% CI: 1.95, 10.2), and heard about cervical cancer (AOR: 2.6, 95% CI: 1.05, 6.41) were associated with cervical cancer screening service utilization. Conclusion The magnitude of cervical cancer screening service utilization was low. It was associated with occupation status, family history of cervical cancer, awareness about cervical cancer screening, history of STI, and ever heard about cervical cancer. Thus, to maximize utilization, health education programs and other multidisciplinary strategies had to be implemented.